Simple and effective strategies to generate diverse designs for truss structures. (August 2021) - Cai, Qi; He, Linwei; Xie, Yimin; Feng, Ruoqiang; Ma, Jiaming
Abstract: Structural topology optimization plays an important role in obtaining conceptual designs in the preliminary design stage. However, traditional structural optimization methods can only generate one optimized design for the material distribution under certain constraints. The optimized structure could have some disadvantages, such as an unattractive appearance, difficulty in manufacturing, or high construction cost. Therefore, it is more practical to produce multiple designs that not only have high structural performance but also have substantially different forms from which the designer can choose. Two strategies were explored in this study for generating diverse truss structures, namely, the penalizing length method (PLM) and the modifying ground structure method (MGSM). Using the proposed PLM, it is possible to delete unneeded bars in the optimized structure, such as very slender bars, and the cross-sectional areas of the remaining bars will be automatically redistributed to ensure structural nodal stability. In addition, by generating overlapping potential bars in the ground structure, the structural instability problem caused by pin joints can be overcome. Two-dimensional and three-dimensional numerical examples were provided to indicate the effectiveness of the proposed methods. The numerical results showed that the proposed methodologies can generate diverse structures while maintaining structural performance.